The individual and the social order in Mill and Hegel : seeking common principles in liberal and communitarian ancestry - Koseff, Justin Adam (Rhodes University, Faculty of Humanities, Department of Political Studies, 2003)
This thesis seeks to establish a significant commonality and compatibility between the principles underpinning the political and social philosophies of GWF Hegel and John Stuart Mill. The role of the individual and the social order in both their theories is discussed and assessed separately and in turn in reference to their respective seminal works on the proper structure, principles and function of modern political infrastructure. Through an interpretation of the fundamental tenets and goals of their theories of the social order I argue for a coherent modern reconstruction of their doctrines, within which I locate parallels and contrasts as they apply. Both theorists as ultimately put forward similar arguments for freedom as an intersubjectivelyÂ·developed capacity, the ideal social order as rational framework for the management of ethical and political engagement, linked to a social holism that ties individual and social progress inextricably. A respect for individual particularity of perspective and practice is integral both of their social frameworks, but that such a space must be harmonised within a rational political community worthy of individual obligation. Finally their social and political theories can be understood as complementary, each providing insights which the other lacks. Mill suffers from an insufficient regard for the social basis of identity and interconnected nature of the modern institutional framework, while Hegel displays an insufficient regard for Mill's caveats concerning the repressive potential of institutional structures and the dangers of overly empowered bureaucracies. In conclusion key elements of the two theorists' projects stand as separate but not in any way fundamentally opposed to each other. This points to the possibility of a via media between a politics of individualism and a politics of community, suggesting strong potential for reconciliation between liberal and communitarian perspectives.
Keywords: Hegel, Georg Wilhelm Friedrich, 1770-1831; Mill, John Stuart, 1806-1873; Liberalism; Communitarianism